Current trends in contrastive linguistics : functional and cognitive perspectives - Gonzalez, Maria de los Angeles, 1971-; Mackenzie, J. Lachlan; González Álvarez, Elsa (Studies in functional and structural linguistics, 2008)
Drawing on data extracted from the British National Corpus and the Corpus de Referencia del Español Actual in conjunction with elicitation data from native speakers, this chapter constitutes a first step towards a constructionist, usage-based analysis of secondary predication with verba dicendi et declarandi (e.g., say, declare, decir 'say', declarar 'declare') in English and Spanish. Within this environment (the "declarative subjective-transitive" construction), at least three lower-level (i.e., item-specific) configurations can be posited in th